HEALTH INSURANCE CLAIMING PROCESS–AN OVERVIEW IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
A family and an Individual can lead a peaceful life when they live a healthy life without having toworry about any unexpected medical issues. Unexpected medical needs may adversely effect on financialcommitments, leads to immediate cash flows and claim in right time. This savings are achieving our long termfinancial goals, So Health insurance overcomes such limitations. This health insurance will help in maintainingthe good health without disturbing the financial stability. Health insurance policies are available that offer bothindividual and family coverage.With health issues becoming more complex in nature now-a-days it hasbecome a necessity to plan for your health.